A Multi-Criteria Decision-Making Approach for Sustainable Energy Prioritization - Mohsen Rezaei (Environmental Energy and Economic Research)
Iran’s economy is highly dependent on energy exports and applying renewable energy (RE) resources is vital to optimize consumption function. The country has a high potential of REs, however, they have been long neglected because of several reasons including abundant natural gas and oil reserves. This study introduces and evaluates main plausible RE resources for the future of sustainable development in Iran. The goal is to investigate and rank Iran’s main RE sources (biomass, geothermal, hydropower, solar PV, and wind). Criteria like technical, economic, environmental, and social are identified and subsequently used for evaluations. A new hybrid MCDM model based on analytic hierarchy process (AHP) and combined compromise solution (CoCoSo) methods is adopted to identify and select the main RE resource. The results indicate that solar PV possess the highest priority, while the economic criterion is the most effective to be considered. The results can help the decision-makers in the field of energy for more accurate planning and strategic management.